2017
DOI: 10.1007/s40858-017-0183-z
|View full text |Cite
|
Sign up to set email alerts
|

Competitive and colony layer formation ability as key mechanisms by yeasts for the control Botryosphaeria dothidea fruit rot of mango

Abstract: Mango is an economically important fruit crop in Brazil and attacked by fungal diseases that require control. Currently, ensuring that fruit are free of pesticide residues before consumption is a key challenge in postharvest pathology. The fungus Botryosphaeria dothidea is the major pathogen and there is currently no efficient method for its control. This work aimed to evaluate the efficacy of yeast strains and the mechanisms involved in the biocontrol of mango rot caused by B. dothidea. The ability of seven y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Representatives are, for example, Candida sake CPA-1 [ 67 ], Candida pseudolambica W16 [ 13 ], Candida albicans [ 68 , 69 ], Candida oleophila [ 70 ], Candida pyralidae Y63 [ 71 ], Candida tropicalis [ 72 ], Candida subhashii [ 73 ], which are envisaged as biological control agents to control mold and postharvest diseases in pome, stone fruits as well as citrus fruits. Its antagonistic effect has been tested to be effective in most fruits, including apple [ 74 ], mango [ 75 ], orange [ 41 ], grape [ 76 ], banana [ 77 ], tomato [ 78 ], citrus [ 79 ], litchi [ 80 ], peach [ 13 ], etc. One study showed that C. sake was effective in controlling Penicillium digitatum , a common post-harvest pathogen in pome fruits [ 40 ].…”
Section: Biocontrol Of Yeasts In Agricultural Productsmentioning
confidence: 99%
“…Representatives are, for example, Candida sake CPA-1 [ 67 ], Candida pseudolambica W16 [ 13 ], Candida albicans [ 68 , 69 ], Candida oleophila [ 70 ], Candida pyralidae Y63 [ 71 ], Candida tropicalis [ 72 ], Candida subhashii [ 73 ], which are envisaged as biological control agents to control mold and postharvest diseases in pome, stone fruits as well as citrus fruits. Its antagonistic effect has been tested to be effective in most fruits, including apple [ 74 ], mango [ 75 ], orange [ 41 ], grape [ 76 ], banana [ 77 ], tomato [ 78 ], citrus [ 79 ], litchi [ 80 ], peach [ 13 ], etc. One study showed that C. sake was effective in controlling Penicillium digitatum , a common post-harvest pathogen in pome fruits [ 40 ].…”
Section: Biocontrol Of Yeasts In Agricultural Productsmentioning
confidence: 99%
“…As a result of the losses caused by these phytopathogens, different control strategies have been suggested, including chemical treatment with pesticides, which are not recommended due to the residues. More recently, the use of the yeast Candida membranifaciens (Terao et al, 2017) has been studied, but there is still no protocol for routine use. Alternatively, essential oils, which are volatile substances, aromatic or odorless, obtained from plant material belonging to the most diverse classes of compounds (Rios, 2016), can present fungistatic and/or fungicide properties, depending on their origin, due to the ability to interact with the cell membrane lipids of microorganisms (Bakkali et al, 2008;Brum et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Meyerozyma guilliermondii was reported as an effective antagonistic yeast, which significantly controlled blue mold decay of pears [6] and controlled rice blast disease, cabbage black leaf spot disorder, and bacterial wilt caused by Ralstonia solanacearum, a tomato pathogen [7]. It also showed significant biocontrol of gray mold disease on table grapes caused by Botrytis cinerea [8] and reduced the severity of rot in mangoes during storage [9]. Our previous study showed that blue mold decay caused by P. expansum was significantly inhibited by M. guilliermondii without any change in the fruit quality [6].…”
Section: Introductionmentioning
confidence: 99%